Clitocybe nuda Activates Dendritic Cells and Acts as a DNA Vaccine Adjuvant. (22nd August 2013) - Chen, Mei-Hsing; Li, Wei-Sung; Lue, Yun-Sheng; Chu, Ching-Liang; Pan, I-Hong; Ko, Ching-Huai; Chen, Der-Yuan; Lin, Ching-Hsiung; Lin, Sheng-Hao; Chang, Chih-Peng; Lin, Chi-Chen
Abstract : This work represents the first evaluation of the effects of water extract of C. nuda (WE-CN), an edible mushroom, on murine bone marrow-derived dendritic cells (BMDCs) and the potential pathway through which the effects are mediated. Our experimental results show that WE-CN could induce phenotypic maturation of DCs, as shown by the increased expression of MHC and costimulatory molecules. In addition, it also induced the proinflammatory cytokines expression on DCs and enhanced both the proliferation and IFN- γ secretion of allogenic T cells. Therefore, since WE-CN did not induce maturation of DCs generated from mice with mutated TLR-4 or TLR-2, suggesting that TLR4 and TLR2 might function as membrane receptors for WE-CN. Moreover, the mechanism of action of WE-CN may be mediated by increased phosphorylation of ERK, p38, and JNK mitogen-activated protein kinase (MAPK) and increased NF- κ B p65 activity, which are important signaling molecules downstream of TLR-4 and TLR-2. Finally, coimmunization of mice with WE-CN and a HER-2/neu DNA vaccine induced a HER-2/neu-specific Th1 response that resulted in significant inhibition of HER-2/neu overexpressing mouse bladder tumor (MBT-2) growth. These data suggest that WE-CN induces DC maturation through TLR-4 and/or TLR-2 and that WE-CN can be used as an adjuvant in cancer vaccine immunotherapy.